Renal autoimmunity: the role of bacterial and viral infections – an extensive review - Lavine, Noy; Ohayon, Aviran; Mahroum, Naim (Academic Press, 2024)
Autoimmunity is a process by which the loss of self-tolerance results in an immune attack against the body own tissues and organs. For autoimmunity to occur, various elements serving as triggers were described by which infections are considered one of the leading factors. In turn, renal involvement in autoimmune diseases, whether by an organ-specific attack, or as part of a systemic disease process, is well known. As bacterial and viral infections are considered to be common triggers for autoimmunity in general, we aimed to study their association with renal autoimmunity in particular. We performed an extensive search of the recent and relevant medical literature regarding renal autoimmunity syndromes such as infection-associated glomerulonephritis and vasculitis, associated with bacterial and viral infections. By utilizing PubMed and Google Scholar search engines, over 200 articles and case reports were reviewed. Among other mechanisms, direct infection of the renal parenchyma, molecular mimicry, induction of B-cells or secretion of superantigens, bacterial and viral pathogens were found to correlate with the development of renal autoimmunity. Nevertheless, this was not true for all pathogens, as some mimic autoimmune diseases and others show a surprisingly protective effect. The exact immunopathogenesis is yet to be determined, however. For conclusion, bacterial and viral infections are linked to renal autoimmunity by both direct damage and as mediators of systemic diseases. Further research particularly on the immunopathogenetic mechanisms of renal autoimmunity associated with infections is required.
Keywords: Iga Nephropathy; Infection-Associated Glomerulonephritis; Renal Autoimmunity; Vasculitis Membranous Nephropathy